Chromophobe Renal Cell Carcinoma With Retrograde Venous Invasion and Gain of Chromosome 21: Potential Harbingers of Aggressive Clinical Behavior. (September 2018) - Jamal, Mohsin; Taneja, Kanika; Arora, Sohrab; Barod, Ravi; Rogers, Craig G.; Sanchez, Jessica; Gupta, Nilesh S.; Williamson, Sean R.
Occasionally, renal cell carcinoma (RCC) with renal vein extension spreads against the flow of blood within vein branches into the kidney, forming multifocal nodules throughout the renal parenchyma. These foci are not regarded as multiple tumors but rather reverse spread of tumor along the venous system. This intravascular spread has previously been reported in clear cell RCC and RCC unclassified. However, to our knowledge, this has never been reported in chromophobe RCC. Chromophobe RCC is a unique histologic subtype of renal cancer, generally thought to have less aggressive behavior. However, it nonetheless has the potential to undergo sarcomatoid dedifferentiation, which is associated with poor prognosis. We report a unique case of a 65-year-old man with chromophobe RCC (pT3a) showing classic morphology (nonsarcomatoid), yet presenting with retrograde venous invasion and hilar lymph node metastasis at the time of right radical nephrectomy. Fluorescence in situ hybridization revealed gain of chromosome 21 with loss of multiple other chromosomes. Partial hepatectomy was performed to resect metastatic RCC 7 months after nephrectomy, revealing chromophobe RCC with classic morphology. Bone biopsy confirmed skeletal metastases 38 months after initial diagnosis. Although invasion of the renal vein and retrograde venous invasion are characteristically seen in clear cell RCC, this unusual phenomenon may also occur in chromophobe RCC, despite its unique tumor biology. This and gain of chromosome 21, which was postulated to be associated with aggressive behavior in a previous report, were associated with adverse behavior in our patient, who had short-term progression to multi-organ metastatic disease.